Biomedical computing for breast cancer detection and diagnosis - Santos, Wellington Pinheiro dos; Silva, Washington Wagner Azevedo da, 1979-; Santana, Maira Araujo de, 1995- (Premier reference source, 2021)
"This book presents a review of the physiology and anatomy of the breast; the dynamics of breast cancer; principles of pattern recognition, artificial neural networks, and computer graphics; and the breast imaging techniques and computational methods to support and optimize the diagnosis"--